Treatments for subacute cough in primary care: systematic review and meta-analyses of randomised clinical trials - Speich, B; Thomer, A; Aghlmandi, S; Ewald, H; Zeller, A; Hemkens, L (Royal College of General Practitioners, 2018)
Background Subacute cough following an unspecific viral infection lasting 3 to 8 weeks is common. Aim To provide a systematic overview of treatment options and outcomes evaluated in randomised clinical trials (RCTs). Design and Setting Systematic review and meta-analyses Method We systematically searched PubMed/MEDLINE and the Cochrane Central Register of Controlled Trials (last search March 2017) for RCTs in adult patients with subacute cough. We considered trials evaluating any outcome of any drug or non-drug treatments apart from traditional Chinese and Asian medicines. We combined treatment effects on cough-related outcomes in random-effects meta-analyses. Results 6 eligible RCTs including 724 patients were identified. They assessed montelukast, salbutamol plus ipratropium-bromide, gelatine, fluticasone propionate, budesonide, nociception-opioid-1-receptor agonist and codeine. 5 studies reported effects on various cough severity scores at various time-points. No treatment option was associated with a clear benefit on cough recovery or other patient-relevant outcomes in any of the studies or in meta-analyses for cough outcomes at 14 and 28 days. Reported adverse events were rather mild and reported for 14% of patients across all treatments. Conclusions Evidence on treatment options for subacute cough is weak. There is no treatment showing clear patient-relevant benefits in clinical trials.